Perbandingan Luaran Open Surgical Repair dan Endovascular Aneurysm Repair pada Pasien Aneurisma Aorta Abdominalis di Asia - Aritonang, Ochta C.; Tangel, Stephanus J. C.; Lengkong, Andriessanto C. (e-CliniC, 2026)
Abstract: Abdominal aortic aneurysm (AAA) is a pathological dilation of the aorta that carries a risk of rupture and high mortality. Two methods of AAA management are Open Surgical Repair (OSR) and Endovascular Aneurysm Repair (EVAR). However, comparative data on the outcomes of these two methods in Asia is still limited. This study aimed to analyze the comparison of OSR and EVAR outcomes in AAA patients in Asia, including length of hospital stay, mortality, complications, and reintervention. This was a systematic review study using articles searched in the Epistemonikos, PubMed, Sage Journals, and ScienceDirect databases. The results obtained a total of 18 articles that met the inclusion and exclusion criteria based on the PICOS framework were obtained. The analysis was performed descriptively on postoperative outcome data. EVAR showed a significantly shorter length of hospital stay compared to OSR, but was accompanied by higher rates of reintervention and long-term complications, such as endoleak. Conversely, OSR was superior in terms of long-term durability and stability. The 30-day mortality rates showed inconsistent and statistically insignificant results. In conclusion, EVAR provides better short-term outcomes, while OSR is more reliable for the long term. The choice of method should consider the patient's condition. Keywords: abdominal aortic aneurysm; Open Surgical Repair; Endovascular Aneurysm Repair   Abstrak: Aneurisma aorta abdominalis (AAA) merupakan dilatasi patologis aorta yang berisiko ruptur dan menimbulkan mortalitas tinggi. Terdapat dua metode dalam penatalaksanaan AAA yaitu Open Surgical Repair (OSR) dan Endovascular Aneurysm Repair (EVAR), namun, data perbandingan luaran keduanya di Asia masih terbatas. Penelitian ini bertujuan untuk menganalisis perbandingan luaran OSR dan EVAR pada pasien AAA di Asia yang meliputi lama rawat inap, mortalitas, komplikasi, dan reintervensi. Jenis penelitian ialah systematic review dari artikel-artikel yang ditelusuri pada basis data Epistemonikos, PubMed,  Sage Journals, dan ScienceDirect. Didapatkan sebanyak 18 artikel yang memenuhi kriteria inklusi dan eksklusi berbasis PICOS framework. Analisis dilakukan secara deskriptif terhadap data luaran pascaoperatif. EVAR menunjukkan lama rawat inap yang lebih singkat secara bermakna dibandingkan OSR, namun disertai angka reintervensi dan komplikasi jangka panjang, seperti endoleak, yang lebih tinggi. Sebaliknya, OSR unggul dalam durabilitas dan stabilitas jangka panjang. Tingkat 30-day mortality menunjukkan hasil yang tidak konsisten dan tidak bermakna secara statistik. Simpulan penelitian ini ialah EVAR memberikan hasil jangka pendek lebih baik, sedangkan OSR lebih andal untuk jangka panjang. Pemilihan metode perlu mempertimbangkan kondisi pasien. Kata kunci: aneurisma aorta abdominalis; Open Surgical Repair; Endovascular Aneurysm Repair